2022
DOI: 10.4103/jmss.jmss_58_20
|View full text |Cite
|
Sign up to set email alerts
|

Fine motor assessment in upper extremity using custom-made electronic pegboard test

Abstract: A fine motor test involves the manipulation of smaller objects with fingers, hands, and wrists. This test is an integral part of the evaluation of an upper extremity function. Nine Hole Peg Test (NHPT) is one among such tests which assess the ability to manipulate pegs with the thumb and finger. There is a need to develop a fine motor assessment tool which is reproducible and mimics closely the natural movement of hands. The aim of this work is to develop an electronic pegboard which is easy to administer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…First, the system can assess not only a motor task, but also a motor-cognitive dual-task as an all-in-one test. Some similar digital pegboards with precise automated time calculation [17,18] aimed only at assessing dexterity based on the conventional pegboards. Petrigna et al [26] have reported that the 25-hole GPT, which involves placement of keyhole-shaped pegs, performed in a dual-task situation is a feasible test to evaluate manual dexterity.…”
Section: Comparison Between E-peg and Other Analog/mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the system can assess not only a motor task, but also a motor-cognitive dual-task as an all-in-one test. Some similar digital pegboards with precise automated time calculation [17,18] aimed only at assessing dexterity based on the conventional pegboards. Petrigna et al [26] have reported that the 25-hole GPT, which involves placement of keyhole-shaped pegs, performed in a dual-task situation is a feasible test to evaluate manual dexterity.…”
Section: Comparison Between E-peg and Other Analog/mentioning
confidence: 99%
“…Recently, some studies reported epochal digital devices. A custom-made electronic pegboard test using an infrared sensor and microcontroller based on the NHPT [17] and a prototype of an electronic version of the GPT [18] have been developed. These electronic pegboards automate precise time calculation, but they were based on traditional pegboards and only focused on hand manipulation assessments.…”
Section: Introductionmentioning
confidence: 99%
“…In this initial experimental trial, none of the participants were able to complete the tasks within the designated time, suggesting that there is room for improvement in terms of the time settings of the prototype. In the next phase of study, we plan to focus on refining and enhancing these aspects [41,42].…”
Section: Evaluation Of Usability Appeal and Difficultymentioning
confidence: 99%
“…Accidents, injuries, or diseases can lead to limitations in hand function, which need to be assessed in the health care setting. Hand assessment involves a systematic evaluation to quantify and assess the quality of a person’s hand function [ 2 ].…”
Section: Introductionmentioning
confidence: 99%